Development of a Blockchain-Based Sustainable Agriculture Supply Chain System: A Study on Horticultural Commodities - Fariah, Aen (Politeknik Siber Cerdika Internasional, 2025)
This research aims to study and develop a sustainable horticultural supply chain system based on blockchain technology in Indonesia. The background of the research is based on the urgent need for transparency, efficiency, and sustainability in managing the distribution of horticultural products that have been facing various challenges, such as data manipulation and limited product tracking. Using a descriptive qualitative approach through case studies in Bandung and Garut Regencies, data was obtained through in-depth interviews, participatory observation, and questionnaires with farmers, distributors, agritech providers, and policy makers. The results showed that blockchain implementation was able to improve traceability by 95%, distribution efficiency by 15%, and reduce operational costs by 25%. The blockchain system is also proven to strengthen trust between supply chain actors and increase transaction accountability. However, there are still obstacles in the form of low understanding of technology at the grassroots level and limited digital infrastructure. This research recommends the integration of blockchain with digital training and cross-sector collaboration to create an inclusive, adaptive, and sustainable agricultural system.